The effect of resin and ball size on the throwing velocity - Dias Estriga, M. L.; Ribeirinha Cardoso de Lima Lobo, H.; Rezende Vieira, I. C. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
This research comprised two preliminary studies about the effect of resin and ball size on the throwing velocity. Our preliminary results suggest that for senior male players, banning the resin usage should be accompanied by a downsize of the ball if similar shooting velocities - and general game characteristics - are to be preserved. The resin usage amounts to an effect on speed (a gain) of about 9% when shooting with the ball size 3.